(untitled) (Élisée - Revista de Geografia da UEG, 2021)
From food to heritage: the importance of valorizing the cassava flour of the coast of Paraná, Brazil Abstract: With an extensive and quite diverse territory, Brazil is also rich in food products, which includes the practices and savoir fare inherent in the systems in which they are produced. This knowledge is the basis on which intangible cultural heritage is produced and reproduced, such as the varieties of the cassava flour are. The characteristics of these territories are the focus of the geographical indications system (IG). Considering the similarities shared by heritage and the IGs, this article aims to investigate the process of obtaining this distinctive sign, especially with regard to the possibilities of valorizing the cassava flour as a cultural asset that makes up the gastronomic cultural heritage of the coast of the Paraná state, Brazil. Bibliographic and documentary research were used as methodological procedures in addition to semi-structured interviews. The cassava flour produced in the coast of Paraná, besides being a differentiated product that can stand out before the consumer market, can be attributed both a better monetary value and a symbolic-cultural value through geographical indications due to its relevance to local memory and the savoir fare rooted in the territory. The recognition of the cassava flour as geographical indication can represent a means of maintaining it not only as part of the basic regional food, but also as a source of income for small farmers in a territory where there are restrictions to types of economic activities that can be developed. Above all, such recognition is an aid to the valorization of cultural practices that are characteristic of the Paraná’s coast. Keywords: Cassava; flour; Cultural heritage; Geographical Indication; Paraná; Brazil.